IMPLIKASI UNDANG-UNDANG NOMOR 8 TAHUN 2015 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 1 TAHUN 2015 TENTANG PENETAPAN PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG NOMOR 1 TAHUN 2014 TENTANG PEMILIHAN GUBERNUR, BUPATI, DAN WALIKOTA MENJADI UNDANG-UNDANG TERHADAP PENYELESAIAN SENGKETA HASIL PEMILIHAN KEPALADAERAH DI MAHKAMAH KONSTITUSI - Arif Ramadhan Sy; Mexsasai Indra; Abdul Ghafur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Local elections democratically elected as mandated by the Constitution of the Republic of Indonesia, to prioritize the people's democratic sovereignty so dilaksanakanlah local elections directly elected by the people. The elections based on Law No. 8 of 2015 held simultaneously. Implementation of simultaneous elections in 2015 led to the implications for the Constitutional Court and also has implications for the judgments of the Constitutional Court.The conclusions in this study, First, some things that have implications on Law No. 8 of 2015 in the Constitutional Court that the buildup of cases in the Court, when the settlement is only 45 days in the Constitutional Court, filing an application for a maximum of 3 x 24 hours, and terms petition filing that is the difference in vote totals at most 2 percent. Second, There are three (3) things that have implications on the judgments of the Constitutional Court on the settlement of election disputes, namely, implications on the Constitutional Court itself, have significant implications for candidates who dispute and also the electoral commission local area, and impilcations for local area influential for the wheels of local government in the dispute. Advice writer, first, not the accumulation of cases the need for special court established to resolve election disputes so that the completion of election disputes more effective, Second, to avoid the occurrence of a Constitutional Court ruling does not lead to justice the Constitutional Court to take a decision in election disputes this should really consider that it is a matter of dispute the local elections is indeed in violation of the TSM so no results.Keywords: Implications – Law Number 8 In 2015 – To Guardian Constitutional